2016
DOI: 10.1093/mnras/stw745
|View full text |Cite
|
Sign up to set email alerts
|

Supernova feedback in a local vertically stratified medium: interstellar turbulence and galactic winds

Abstract: We use local Cartesian simulations with a vertical gravitational potential to study how supernova (SN) feedback in stratified galactic discs drives turbulence and launches galactic winds. Our analysis includes three disc models with gas surface densities ranging from Milky Way-like galaxies to gas-rich ultra-luminous infrared galaxies (ULIRGs), and two different SN driving schemes (random and correlated with local gas density). In order to isolate the physics of SN feedback, we do not include additional feedba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(143 citation statements)
references
References 70 publications
9
134
0
Order By: Relevance
“…Overall, we find a very good correlation between η E and the ISM condition: η E 0.08 when ISM is "breakout"; η E 0.01 when ISM is "non-breakout"; η E ∼ 0.01-0.08 when ISM is "partial-breakout". We note that "partial-breakout", in reality, can either be due to the final, quasi-steady ISM state falling into the criterion (Martizzi et al 2016), or the ISM transitioning/cycling between the non-breakout and the breakout states (Kim & Ostriker 2018).…”
Section: Sfrmentioning
confidence: 99%
“…Overall, we find a very good correlation between η E and the ISM condition: η E 0.08 when ISM is "breakout"; η E 0.01 when ISM is "non-breakout"; η E ∼ 0.01-0.08 when ISM is "partial-breakout". We note that "partial-breakout", in reality, can either be due to the final, quasi-steady ISM state falling into the criterion (Martizzi et al 2016), or the ISM transitioning/cycling between the non-breakout and the breakout states (Kim & Ostriker 2018).…”
Section: Sfrmentioning
confidence: 99%
“…For our model we account for the entire galactic disc, although this imposes constraints on the spatial resolution we can afford. As was pointed out by Martizzi et al (2016), not accounting for the global geometry of the disc, as is the case for ISM patches, leads to unreliable wind properties due to incorrect treatment of the gravitational potential and the disc rotation.…”
Section: Comparison To Other Workmentioning
confidence: 99%
“…Several decades of research in this area have identified stellar feedback as one of the leading physical processes to explain this inefficiency in L * galaxies and below (e.g. Stinson et al 2006;Sales et al 2010;Ostriker & Shetty 2011;Hopkins et al 2014a;Kimm & Cen 2014;Marinacci et al 2014;Vogelsberger et al 2014;Murante et al 2015;Wang et al 2015;Schaye et al 2015;Martizzi et al 2016;Li et al 2017;. Resolving the multiphase structure of the ISM and a detailed modelling of stellar feedback are therefore key targets in modern studies of galaxy formation.…”
Section: Introductionmentioning
confidence: 99%